Sarcopenia is a Novel Predictor of the Need for Rescue Therapy in Hospitalized Ulcerative Colitis Patients. (12th May 2018) - Cushing, Kelly C; Kordbacheh, Hamed; Gee, Michael S; Kambadakone, Avinash; Ananthakrishnan, Ashwin N
Abstract: Background and Aims: Acute severe ulcerative colitis [ASUC] affects one in four patients with UC. Clinical parameters perform modestly in predicting the need for rescue therapy. Sarcopenia and visceral adiposity predict natural history in Crohn's disease, but the role of such metabolic factors on ASUC outcomes is unknown. The aim of this study was to define the effect of sarcopenia and visceral adiposity on outcomes in ASUC. Methods: We studied patients hospitalized for ASUC who underwent an abdominal CT scan during the hospitalization. Quantification of skeletal muscle mass and visceral adiposity was performed by radiologists blinded to the outcome. Sarcopenia was defined as a skeletal muscle index of <55 cm 2 /m 2 for men and <39 cm 2 /m 2 for women. The primary outcome of interest was need for medical or surgical rescue therapy. Results: Our study included 89 patients with ASUC, among whom 39 [43.8%] patients required medical rescue therapy or surgery. Two-thirds of the cohort [70%] met the definition of sarcopenia [81% men, 48% women]. Patients with sarcopenia had similar disease characteristics and laboratory parameters to those with a normal muscle mass. However, a larger proportion of patients with sarcopenia required rescue therapy compared with those without (56% vs 28%, multivariable odds ratio [OR] 3.98, 95% confidence interval [CI] 1.12–14.1). Neither visceral [ p = 0.23] nor subcutaneous adiposity [ p = 0.53] predicted the need for rescue therapy. Conclusions: Sarcopenia as determined on abdominal CT was a novel predictor of need for rescue therapy in hospitalized UC patients.